Copper nitrate-mediated synthesis of 3-aryl isoxazolines and isoxazoles from olefinic azlactones. Issue 22 (21st May 2019) - Lin, Yifan; Zhang, Ke; Gao, Mingchun; Jiang, Zheyi; Liu, Jiajie; Ma, Yurui; Wang, Haoyu; Tan, Qitao; Xiao, Junjie; Xu, Bin
Abstract : A copper nitrate-mediated [2 + 2 + 1] cycloaddition reaction was developed for the expedient synthesis of isoxazolines and isoxazoles from olefinic azlactones. Abstract : A copper nitrate-mediated [2 + 2 + 1] cycloaddition reaction was developed for the expedient synthesis of pharmacologically interesting 3-aryl substituted isoxazolines and isoxazoles through CC bond cleavage. Copper nitrate is employed as a reaction promoter and precursor of nitrile oxides. The given approach features a new mode of cycloaddition from olefinic azlactones, copper nitrate and unsaturated compounds with wide substrate scope, good functional group tolerance and operational simplicity.